CLINICAL AND ECONOMIC EFFECTIVENESS OF SIMULTANEOUS SURGERY IN PATIENTS WITH COMBINED GYNECOLOGICAL PATHOLOGY - Kondratiuk, N.Yu.; Lysenko, B.M.; Struk, T.A.; Tkachenko, R.P.; Kuryk, O.G.; Pasichnik, G.P.; Sheptukha, S.A. (World of Medicine and Biology, 2022)
The problem of simultaneous operations in gynecological practice is quite relevant. The purpose of the study was to determine the clinical and economic efficiency of simultaneous operations in patients with combined gynecological pathology. We performed a retrospective analysis of the results of the surgical treatment of 50 women with a combination of several gynecological diseases, each of which required surgical treatment. Calculations were made according to the following parameters: cost of preoperative examination, pre- and postoperative medical care, operative care, anesthesia care, and postoperative laboratory monitoring. The analysis of the studies shows that simultaneous operations shorten the length of the patient's stay in the hospital and the duration of temporary incapacity by two to three times, increase the economic efficiency of treatment by three times and improve their quality of life. Carrying out simultaneous operations on women with combined gynecological pathology allows a rational use of the material and technical base of the medical institution. Also, it leads to significant financial savings at the hospital and outpatient stages.
Keywords: simultaneous operations; reproductive health; hysteroscopic myomectomy; effectiveness of medical care; colporrhaphy